The Journey is Individual; You Are the Shepherd, and You Are the Flock. Towards An Autonomy-Based Model to Underpin the Legal Rules of Informed Consent in Medical Treatment in Saudi Jurisdiction: A Normative Analysis from Shari'a Perspective - Alhusayni, Nourah Hamad (Trinity College Dublin. School of Law. Discipline of Law, 2025)
From a Sharia perspective, this thesis employs the normative legal method to analyse the moral foundations of trust and autonomy underlying the legal rules of medical consent in Saudi law. It identifies that maintaining good health is significant in Sharia and that the current Saudi approach has adopted the principle of trusting physicians to make medical decisions in the best interests of patients' health. Having concluded that trust in physicians has shifted into paternalistic behaviours that fundamentally undermine the moral construct of trust in Sharia discourse, and most importantly, in Sharia discourse, the responsibility for maintaining good health is placed squarely on individuals themselves. The thesis, therefore, analyses the principle of autonomy and whether a movement to an autonomy model would be compatible with Sharia principles. The thesis argues that the principle of autonomy is significant in medical decision-making when the patient's health is concerned. Such relevance stems from the Islamic theological doctrine of taklif, derived from the Islamic framework of dignity associated with humanity's vicegerency on earth, which asserts that the core qualities of humans to fulfil the mission of vicegerency while bearing taklif are rationality, cognitive abilities and free will that enable individuals make moral and autonomous decisions when it comes to their health. Ultimately, patient autonomy must be respected and maximised, as patients are morally responsible for their actions.
APPROVED